2017
DOI: 10.1016/j.socec.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Do higher achievers cheat less? An experiment of self-revealing individual cheating

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
1
11
1
Order By: Relevance
“…Bloodgood et al (2010) showed that students scoring high on Machiavellianism were more tolerant of cheating in general compared to other students. Contrary to previous research, Yaniv, Siniver & Tobol (2017) concluded that higher-achieving students were bigger cheaters. Hendy (2017) found that more conscientious students cheated less often compared to less conscientious students.…”
Section: Determinants Of Cheatingcontrasting
confidence: 81%
“…Bloodgood et al (2010) showed that students scoring high on Machiavellianism were more tolerant of cheating in general compared to other students. Contrary to previous research, Yaniv, Siniver & Tobol (2017) concluded that higher-achieving students were bigger cheaters. Hendy (2017) found that more conscientious students cheated less often compared to less conscientious students.…”
Section: Determinants Of Cheatingcontrasting
confidence: 81%
“…Furthermore, although the odds of students whose GPA level in 2.01-2,5 was one-third of students whose GPA level bigger than 3.5, it was statistically significant. We have little evidence to state that our findings confirmed the previous research result, i.e., higher achievers are bigger cheaters (Yaniv et al, 2017). This current study indicated that GPA factor was confounded by gender variable, and alternatively, GPA factor increased the effect of gender variable in making the justification for immoral behaviour.…”
Section: Moral Reasoning and Gendersupporting
confidence: 66%
“…Most of them have examined this topic within the scope of academic behavior. In the educational environment, immoral behavior such as cheating or plagiarism arises because students 'quality' is only understood and placed on cognitive processes (Cartwright & Menezes, 2014;Yaniv, Siniver, & Tobol, 2017). There is a latent recognition that curriculum deals with cognitive aspects, while extra-curriculum deals with character development.…”
Section: Introductionmentioning
confidence: 99%
“…Hilbig & Zettler (2015) underpin these findings by showing that honesty-humility accounted for a large proportion of the variance in dishonest behavior across six experiments that varied in incentive structure, mode of data collection and sample composition. But also more distant individual factors affect cheating, as, for example, Yaniv et al (2017) find that high achievers, measured through students' GPA, tend to cheat more than students with a lower GPA.…”
Section: Research On Personality and Moral Charactermentioning
confidence: 99%